PENGARUH MODEL PEMBELAJARAN KONSIDERASI DALAM MENINGKATKAN SIKAP SPRITUAL SISWA - Penti Suryani; Ismail Sukardi; Abu Mansur; Septia Fahiroh (PAI RAFAH, 2022)
The purpose of this study was to determine the effect of the consideration learning model in improving students' spiritual attitudes in Akidah Akhlak class VII at MTs YPNH Tanah Abang. This research uses quantitative research with the type of Two-group Post-Test-Only Design. This type of research uses data collection methods used are observation, questionnaires, and documentation. Data analysis techniques using the t-test. The results showed that the spiritual attitude of students in the experimental class using the consideration learning model was classified as a moderate category, namely with an average value of 71,.75, meaning moderate here in achieving indicators of spiritual attitude has not been achieved as expected. While the spiritual attitude of students in the control class using the concessional learning model is classified as low, namely with an average value of 62.25, the meaning is low here in achieving indicators of spiritual attitudes not maximally achieved as expected. Based on the results of hypothesis testing using the t-test formula, it can be seen that at the 5% level and at the 1% level t count> t table, namely t count 4.54 and t table 1.99 (5% level) and 2.65 (1% level). Thus it can be concluded that the alternative hypothesis (Ha) is accepted which shows that there is a significant difference between the spiritual attitudes of experimental class students and the spiritual attitudes of students in the control class.